APLIKASI PENINGKATAN ADMINISTRASI DAN KOORDINASI BERBASIS DIGITAL PADA SEKRETARIAT DAERAH KABUPATEN NIAS UTARA - Sehati Zendrato; Maria Magdalena Bate'e; Ardin Gea; Idarni Harefa (Jurnal Publikasi Manajemen Informatika, 2026)
administration still dominates organizational document management and creates various obstacles such as slow distribution, difficulties in archive retrieval, weak interdepartmental coordination, high operational costs, as well as low transparency and data security. This condition contradicts the demands of modern administration, which emphasizes the use of information technology. This study aims to design a digital-based application to improve administrative efficiency, analyze the application’s contribution to interdepartmental coordination, identify the capability of digital systems in overcoming the weaknesses of manual management, and assess the alignment of the application with e-Government and SPBE (Electronic-Based Government System) principles. The research applied a qualitative approach through in-depth interviews with key informants and document studies, with thematic analysis based on modern administration theory, digital coordination, and SPBE regulations. The findings show that administrative digitalization through digital correspondence recording, integrated archive search, automatic notifications, data backup, and audit trail can overcome the weaknesses of the manual system. Digitalization has been proven to accelerate document distribution, simplify archive retrieval, enhance transparency, strengthen accountability, reduce operational costs, and improve interdepartmental coordination. The implementation of digitalized administration results in a significant transformation from a manual system that is slow, wasteful, and less accountable to a digital system that is faster, more efficient, transparent, secure, and cost-effective. The success of implementation is determined not only by technical aspects but also by compliance with SPBE regulations. Digitalization has been proven to positively impact the improvement of public service quality and organizational effectiveness.